First year graduate teaching assistants: fostering successful teaching - Hernandez, Gabriela Maria, author; Pilgrim, Mary, advisor; Ellis, Jessica, committee member; Doe, Sue, committee member; Gingerich, Karla, committee member (Colorado State University. Libraries, 2017)
The importance of effective graduate teaching assistant (GTA) training is often greatly under appreciated. However, it is imperative that GTAs receive optimal professional development because they are often responsible for teaching undergraduate courses. Furthermore, as many GTAs move on to be faculty, inadequate GTA professional development will lead to an inadequate generation of faculty. With incentive to optimize the professional development of the next generation of faculty, as well as to help retention rates of undergraduate students, the quality of GTA training should be a top priority for many universities. This study was conducted for the purpose of making recommendations for the GTA training program in the mathematics department at a research university.
Keywords: GTA; training; mathematics education; culture